Non-Hodgkin’s Lymphomas and AIDS - Silva, Marisa (2003)
Non-Hodgkin’s lymphoma occurs among all population groups at risk for HIV infection, in all age groups and in different countries, with similar epidemiologic and clinico-pathologic features. Clinical presentations may include systemic lymphoma, primary CNS lymphoma, and primary effusion lymphoma. Recent investigations have led to the identification of a particular type of AIDS-related non-Hodgkin’s lymphoma defined as plasmablastic lymphoma of the oral cavity.Systemic AIDS-NHL are a heterogeneous group of malignancies displaying a B-cell phenotype, and at the time of diagnosis approximately 75% of patients have advanced diseasemwith frequent involvement of extra-nodal sites, the most common being the CNS, bone marrow, gastrointestinal tract and liver.Regarding patients followed in the Santo António dos Capuchos Hospital, the authors made a retrospective analysis of systemic AIDS-NHL cases admitted to a Department of Haematology over a six year period. The following parameters were assessed: sex, age, performance status, AIDS-defining conditions prior to the diagnosis, opportunistic infection, CD4 cell count, histology, involvement of the bone marrow and CNS, treatment and evolution.